ANALISIS PENGGUNAAN METODE PEMBELAJARAN TERHADAP MOTIVASI BELAJAR SISWA - Jamaludin, Ujang; Setiawan, Sigit; Putri, Dhara Valia; Fairuz, Rahmi Septia; Khaulani, Qisti (STKIP Persada Khatulistiwa Sintang, 2024)
Education is a planned effort to realize the learning process so that students develop their potential to develop the skills needed by themselves, society, nation and state. In order for learning to be conducted optimally, all learning processes must apply learning methods. The problem that occurs is the low learning motivation of children at SD Negeri Karet 2 which causes learning objectives do not be achieved. It is caused by several factors including the use of lecture learning methods and inadequate infrastructure. The research method is qualitative by applying descriptive analysis techniques. Based on the results of the analysis, it was found that aspects that influence students' learning motivation include the learning methods used. And, aspects that influence students' learning motivation include the willingness, time, obligation and perseverance.